MURINE MODELS FOR THE STUDY OF TRIPLE NEGATIVE BREAST CANCER: MODELOS MURINOS PARA EL ESTUDIO DE CÁNCER DE MAMA TRIPLE NEGATIVO - Cauna Orocollo, Yudith (2024)
ABSTRACT The study of different variables, such as pathogenesis, inflammatory profile, identification of therapeutic targets, efficacy of treatments in murine models has proven to be one of the most practical for the preclinical study of triple negative breast cancer (TNBC), the most aggressive subtype of cancer, with limited application of treatments and low survival rate. However, it must be recognized that there are other minors in which the induction of TNBC is being standardized. This review encompasses the different induction methods that have allowed the development of TNBC and the most relevant therapeutic applications by which murine models with TNBC were developed.